The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12963-016-0114-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes incidence and projections from prevalence surveys in Fiji

Abstract: BackgroundType 2 diabetes mellitus (T2DM) incidence is traditionally derived from cohort studies that are not always feasible, representative, or available. The present study estimates T2DM incidence in Fijian adults from T2DM prevalence estimates assembled from surveys of 25–64 year old adults conducted over 30 years (n = 14,288).MethodsT2DM prevalence by five-year age group from five population-based risk factor surveys conducted over 1980–2011 were variously adjusted for urban-rural residency, ethnicity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Incidence of T2DM was ~90% lower among obese people who do not have any other MetS components, or evidence of IR, inflammation and fatty liver, than among the group with one or more of these metabolic abnormalities. The overall incidence of T2DM in our study is similar to that described in many cohorts from different regions around the world [1,[25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 86%
“…Incidence of T2DM was ~90% lower among obese people who do not have any other MetS components, or evidence of IR, inflammation and fatty liver, than among the group with one or more of these metabolic abnormalities. The overall incidence of T2DM in our study is similar to that described in many cohorts from different regions around the world [1,[25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 86%
“…The high incidence of ESKD in Fiji may be attributable to the very high burden of non‐communicable diseases. Obesity, diabetes and hypertension have increased in Fiji over several decades and are predicted to continue steadily rising . In 2011, the STEPwise approach to Surveillance (STEPS) survey of adults in Fiji found a high prevalence of overweight (32.1%), raised blood pressure ≥140/90 mm Hg (29.6%) and raised fasting glucose (29.6%) .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, diabetes and hypertension have increased in Fiji over several decades and are predicted to continue steadily rising. [21][22][23] In 2011, the STEPwise approach to Surveillance (STEPS) survey of adults in Fiji found a high prevalence of overweight (32.1%), raised blood pressure ≥140/90 mm Hg (29.6%) and raised fasting glucose (29.6%). 24 Our findings with regards to diabetes as the dominant reported cause of ESKD are consistent with this epidemiological data.…”
Section: Eskd In Fijimentioning
confidence: 99%
“…One study reported data on recent trends in DM incidence in Fiji [42], and it showed rates on a constant rise (from 261 per 100,000 in 1980 to 502 per 100,000 per year in 2011) (Fig. 2).…”
Section: Oceaniamentioning
confidence: 99%